Halalfoodies for travelers: a conceptual business model that gives benefits for humans and environments - Noorhamidi, Nurul Syakilah; Mohd Yusri, Yusrina; Zulkifli, Suzanna; Ahmad Dahlan, Abdul Rahman (Research publish, 2020)
The objective of this paper is to reintroduce a business model canvas for a food delivery platform that is aligned to the United Nations Sustainable Development Goals (SDG). The platform harnesses the rapid advancement of the Industrial Revolution 4.0 (IR) technology as well as human adaptation towards technology infrastructure and digital capabilities in the food delivery business. This paper identified several key problems and pains of the Customer Segments in the current food delivery system business model that ought to be solved. The key problems include the lack of diversification of halal foods in non-Muslim countries (SDG 2), unemployment issue (SDG 4&8) and poverty among the Muslim community (SDG 1). The methodologies used in this paper is design thinking methodology. The methodology is carried out by using business modelling tools which are Literature Review, Business Model Canvas (BMC), strategy canvas (SC), Value Proposition Design Canvas (VPC), Environmental Map, future work, and Business Plan. From the validation of the BMC and VPC presented in the paper, the key findings are HalalFoodies business model and app can help them to ease the finding of halal food while traveling to non-Muslim countries, users also have the ability to perform sadaqah through our app to help needy people and perform the sunnah, and that the platform offers job opportunities to the community. The conceptual business model for this paper includes an enhanced Business Model Canvas that encompasses additional customer segments which are the B40 group of citizens, and the Non-Government Organizations (NGOs).